O mapeamento da indústria criativa sergipana : sua relação com a propriedade intelectual - Santos, Ana Paula Silva dos (2015)
Intellectual property is an instrument that ensures rights involving essential factors to protection of copyright, inventor, artist, patent, trademarks, etc. The World Intellectual Property Organization - WIPO (1975) defines as Intellectual Property, the sum of the rights to all creation to literary, artistic and scientific works. Adding to this information is a creative industry that involves the sectors related to creativity this fundamental factor to leverage the advancement of craft creation. The objective of this study was to map the Creative Industries Sergipana focusing on the craft and its relationship to intellectual property. Visits were carried out in some institutions such as the Brazilian Service of Support for Micro and Small Enterprises in Sergipe - SEBRAE, San Francisco of the Valleys Development Company and Parnaíba - CODEVASF, National Confederation of Artisans - CONSTRIART and Sergipe Program Handicraft Development - PROARTE, to obtain information about the groups of artisans in the state and acquiring contacts, and finally , there was the applicability of the questionnaire with the artisans of Aracaju and the interior of the Sergipe State. There was a significant potential of Sergipe artisans , especially in relation to creativity , however , these professionals do not have the knowledge about the Intellectual Property or on your copyright in favor to protect , enhance and stimulate craft productivity.